Recent advances in managing Peyronie’s disease - Kayes, Oliver (F1000Res, 2016)
Peyronie’s disease remains an under-reported and debilitating problem which can result in significant physical and psychological symptoms for some men. The classic symptom complex includes penile curvature, penile plaque, and penile pain. Men can also present with erectile dysfunction, penile instability, and penile shortening, alongside feelings of low mood/libido, dysmorphobia, and low self-esteem. This review highlights the current key publications in the medical literature and provides updates on new clinical therapies whilst postulating about potential future treatments on the horizon.